The spacing effect in older and younger adults: does context matter?. Issue 6 (2nd November 2017) - Bercovitz, Katherine E.; Bell, Matthew C.; Simone, Patricia M.; Wiseheart, Melody
ABSTRACT: Age-related memory change has been a topic of much investigation in recent years, including spacing benefits and reliance on contextual cues. We manipulated the spacing schedule and the context of learning and observed the effects on long-term recall ability in healthy older and younger adults. After learning Swahili–English word pairs, half practiced immediately (massed) and half practiced 24 h later (spaced) either in the same room or a different room (context) from the initial session. A final recall test 10 days after the practice session occurred in the same room as the first session. Participants in the spaced condition remembered more than those in the massed condition 10 days later. Younger adults remembered more word pairs than older adult participants. Context change eliminated the spacing benefit for both age groups.